Contradiction between openness, transparency, accountability and confidentiality of information in vietnamese law - Nguyen, Phuong Vy (2020)
Publicity, transparency, and accountability act as basic and essential elements of the modern governance model. These terms carry the minds of its creators with the goal of establishing and maintaining an open, transparent information system. This is also consistent with the inevitable trend of the current 4.0 industrial revolution. In recent years, tens of thousands of Vietnamese business have started and built their business models through the basics of connectivity and sharing. Connection and sharing also becom the basic key that the private sector cares about and expect most from the political system, especially the government, ministries, branches, and management levels from central to local levels.